Analysis of Metabolite Profile of Gambier Flower (Uncaria gambir (Hunter) Roxb.) in Various Solvent Fractions Using LC-MS - Arif Ferdian; Amri Bakhtiar; Suci Salwa Fitri Mustafa; Neny Sandrawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The gambier plant is known as a rich source of secondary metabolites with biological activities, including anticancer, antioxidant, and antimicrobial properties. The leaves of the gambier plant are reported to contain flavonoids, including catechins, and tannins. This study aims to analyze the metabolite profile of gambier flowers using Liquid Chromatography-Mass Spectrometry (LC-MS). Gambier flower samples were extracted by maceration using ethanol as the solvent. The resulting macerate was then fractionated using n-hexane, ethyl acetate, and n-butanol. The gambier flower extracts were tested for phytochemical content via thin-layer chromatography (TLC) and analyzed for secondary metabolite content via LC-MS for each fraction. TLC testing of the total extract yielded positive results for flavonoids, steroids, phenolics, and alkaloids. Analysis of the secondary metabolite profile of the total extract identified 6 compounds from the 14 compound chromatograms that appeared; the n-hexane extract showed 6 compounds successfully identified from a total of 20 compounds, the ethyl acetate extract showed 6 identified compounds from 17 compounds, and the n-butanol extract contained 7 known compounds from 35 compounds. From the metabolite profile analysis, it can be concluded that gambier flowers contain numerous bioactive compounds with potential for further development and can serve as a source of new knowledge in exploring plant potential. To the best of our knowledge, this is the first LC-MS-based metabolite profile of gambier flowers, an organ that has remained largely unexplored compared with the widely studied leaves; the flowers display a greater diversity of flavonoid glycosides and phenolic derivatives, highlighting their novelty and their promise as antioxidant-rich raw materials for the pharmaceutical and cosmetic industries.